Research of Civil and Legal Relations of Kievan Rus Period Made by Professor P. P. Tsitovich (1843-1913) - V. A. Grechenko (Bulletin of Kharkiv National University of Internal Affairs)
The subject matter of the research is the creative work of the professor of Kharkiv, Kyiv, Odesa and St. Petersburg Universities P. P. Tsitovich related to some aspects of the law of Kievan Rus. The novelty of the work is the fact that this problem in the historical and legal literature has not been studied yet. For the first time, the author of the article has studied the main aspects of scientific research accomplished by professor P. P. Tsitovich in the field of civil law of the period of the Old Russian State. The author of this research has used historical, formal and logical methods.